Calcium-regulated adenylyl cyclases and cyclic AMP compartmentalization - Cooper, Dermot (Henry Stewart Talks, 2007)
Calcium-entry, Elements of the compartment: adenylyl cyclases, lipid rafts, PP2A, NHE1, calmodulin and PDE, cAMP kinetics within the compartment in single cells: role of PDE4, PKA and AKAPs, cAMP oscillations